Zibby Payne & the drama trauma - Bell, Alison (Lobster Press, 2007)
Sixth-grade soccer star Zibby gets the lead part in the school musical, then learns that her character has to kiss a boy. What can Zibby do to get out of smooching onstage?
2nd book in the Zibby Payne series.
Keywords: Girls / Juvenile fiction; Girls / Fiction; Musicals / Fiction; Schools / Fiction